Non-pharmacological measures in preterm newborns submitted to arterial puncture - Gleicia Martins de Melo; Maria Vera Lúcia Moreira Leitão Cardoso
ABSTRACT Objective: to assess pain in preterm newborns and to compare the neonatal and therapeutic variables with the total scores of the Neonatal Facial Coding System of preterm newborns submitted to arterial puncture exposed to music and 25% oral glucose. Method: a comparative study with 48 recordings of preterm newborns - Group 1, music (26); Group 2, glucose 25% (22) - individually analyzed by three trained nurses, after Kappa of at least 80%. Results: the variables and the pain scores of the groups did not present statistical significance (p < 0.05) according to the Neonatal Facial Coding System. 80.8% of the preterm infants in Group 1 had a higher quantitative score ≥ 3 in the neonatal variables (gender, type of delivery), and therapeutic variables (type of oxygen therapy, place of hospitalization, type of puncture). Conclusion: There was no difference when comparing the music and glucose 25% groups and the variables studied.